A CROSS SECTIONAL STUDY OF LIPID PROFILE IN NON-DIABETICS WITH STROKE IN URBAN CHITRADURGA - Vijeth, S. B.; Mangasuli, V.; Amrutha, A. M.; Bhoovanchandra, N.; Sidenur, B. (International Journal of Medicine and Medical Research, 2021)
Background. The amount of evidence regarding the relation between serum lipids, lipoproteins and cerebrovascular accident is not adequate. The atherogenecity of diabetics and non-diabetics are different. Therefore, non-diabetic patients were included in the study. Objective. To study lipid abnormalities in non-diabetic stroke patients in our setup. Methods. The study was carried out at the Department of General Medicine, BMCH, Chitradurga, during the period from June 2020 to December 2020. The lipid profile and the fasting blood sugar rates of 50 stroke patients without diabetes were studied. Their serum samples were assessed for fasting blood glucose (FBG), total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL) and high-density lipoprotein cholesterol (HDL) by using standard biochemical methods. Results. The age distribution of the subjects was from 19 to 72 years with a mean age of patients 54.8±15.75 years. Among patients 31 (62%) were males and 19 (38%) were females. Among the study subjects 58% were hypertensive, 76% were smokers, 32% were alcoholics and 34% had family history of cerebrovascular accident. Among ischemic stroke group, the most common deranged value in the ischemic group was decreased HDL deranged in 54.1% of patients; the second most common deranged value – increased VLDL deranged in 40.5%. Among the hemorrhagic group the most common deranged value was also decreased HDL, which was deranged in 46.1% of patients and the second most common deranged value – increased total cholesterol, which was deranged in 53.8% patients. Conclusion. Lipid profile should be considered while predicting the risk of stroke.